Moralitas dan Spiritualitas Pantekosta dalam Kisah Para Rasul 2:1-47: Morality and Pentecostal Spirituality in Acts 2:1–47 - Natanael Winanto; Susanti Embong Bulan (Journal of Religious and Socio-Cultural, 2023)
- Pentecostalism, a movement that lived from the beginning, viewed the first-century church, mentioned in acts, as its paradigm. This study aims to explain morality and Pentecostal spirituality in Acts 2: 1-47. The research method used is literature review of Pentecostal morality and spirituality and Acts 2:1-47. The result is the first part of this article on the paradigm of Acts 2:1-47 which describes the charismatic empowerment of the Holy Spirit, the manifest manifestation of the gift, the mission in terms of spiritualistas. The second part addresses unique aspects of Pentecostal spirituality as a result of the paradigm of Acts 2:1-48. Pentecostal spirituality in Acts 2 is a new interpretation of the phenomenon that occurred in the early church era until today. The phenomenon is alive and moving continuously across the ages. Until finally gave birth to a contemplation, study and gave birth to a new understanding in Christianity. Pentakostalisme, sebuah gerakan yang hidup sejak awal, memandang gereja abad pertama, yang disebutkan dalam Kisah Para Rasul, sebagai paradigmanya. Kajian ini bertujuan menjelaskan moralitas dna spiritualitas Pantekosta dalam Kisah Para Rasul 2:1-47. Metode penelitian yang digunakan adalah kajian literatur moralitas dan spiritualitas Pantekosta dan Kisah Para Rasul 2:1-47. Bagian pertama dari artikel ini tentang paradigma Kisah Para Rasul 2:1-47 yang menggambarkan pemberdayaan karismatik Roh Kudus, manifestasi nyata dari karunia, misi dalam hal spiritualistas. Bagian kedua membahas aspek-aspek unik dari spiritualitas Pantekosta sebagai hasil dari paradigma Kisah Para Rasul 2:1-48. Hasilnya adalah spiritualitas Pantekosta dalam Kisah Para Rasul 2 merupakan pemaknaan baru terhadap fenomena yang terjadi di era jemaat awal hingga saat ini. Fenomena itu hidup dan bergerak terus melintasi zaman. Hingga akhirnya melahirkan sebuah perenungan, pengkajian dan melahirkan pemahaman baru dalam kekristenan.